PERSONAL VALUES DAN INTERNAL POLITICAL EFFICACY TERHADAP PARTISIPASI POLITIK MAHASISWA PEMILIH PEMULA (Studi pada Fakultas Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Fakultas Adab dan Humaniora, serta Fakultas Dakwah dan Komunikasi UIN SGD Bandung) - Elis Anisah Fitriah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2014)
Political participation is the manifest of people power, however there’s a declining trend of voters in the previous elections. This study is aimed to examine relative contribution of personal values and internal political efficacy toward political participation. Subject of research is 231students from four faculties of Islamic State University (UIN) Sunan Gunung Djati Bandung, registered and becaming a novice voter in the election of 2014. The result of the regression analysis between Personal Values (X1) and Internal Political Efficacy (X2) collectively together against participation in Political Participation (Y) is resulted F = 17,809 in the significancy level (p) = 0,000. It shown that Personal Values and Internal Political Efficacy simoultaneously have significant effect toward student’s political participation .